PEMIKIRAN PENDIDIKAN K.H. HASYIM ASY’ARI - Budiman Budiman; Azizah Hanum OK; Nurdalipah Hasugian; Havelia Ramadhani; Muhammad Zulham Munthe (PAI RAFAH, 2022)
This study aims to determine the thought of Islamic education and the contribution of KH. Hasyim Asy'ari. The research method used in this research is the Library Research method, which is a series of activities related to library information collection methods, reading and writing, and processing research material. The data analysis technique that the author uses in this research is content analysis or what is often called content analysis. This content analysis is used to compare one research with other research that is in accordance with this article. It is a research that uses literature sources from articles and journals to obtain research information. This article also discusses the challenges and opportunities in applying K.H. Hasyim Asy'ari's educational thought in the context of modern education. The challenges include the different views and interests in the current education system, while the opportunities lie in the community's need for value-based and character development-oriented education. The results of the study explain that K.H. Hasyim Asy'ari introduced the impact of his appearance on various sides of life, especially in the field of religion, considering the reflection for the field of schooling. The idea of schooling applied by K.H. Hasyim Asy'ari relies on the Qur'an as a worldview that combines three points of view because it depends on God's revelation that a total schooling system with instructive purposes is given, as well as the type of information according to its capabilities. It also incorporates his outstanding works. His considerations on schooling, not through progressive but rather by advancing, in light of the fact that he is hostile to evil who loves harmony.